2021
DOI: 10.1016/j.mayocp.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Abnormalities in COVID-19 and Relationship to Outcome

Abstract: Objective: To characterize the clinical and transthoracic echocardiographic features and 30-day outcomes of hospitalized patients with coronavirus disease 2019 . Methods: Retrospective cohort study that included consecutive inpatients with COVID-19 infection who underwent clinically indicated transthoracic echocardiography at 10 sites in the Mayo Clinic Health System between March 10 and August 5, 2020. Echocardiography was performed at bedside by cardiac sonographers according to an abbreviated protocol. Echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
“…The definition of RVD was heterogeneous across studies, both in terms of parameters and cut-offs used to defined RVD. 13 studies used a combination of several parameters 15 , 18 , 19 , 21 , 24 , 28 , 30 , 33 35 , 38 , 40 , 42 , 8 studies defined RVD according to TAPSE cut-off 14 , 16 , 22 , 23 , 31 , 32 , 36 , 39 , while other or unclear definitions of RVD was used in 8 studies 17 , 20 , 25 27 , 29 , 37 , 41 . In one study, a surrogate of Right Ventricular-Arterial uncoupling, which in turn relates the degree of RVD to the increase of pulmonary pressure, was addressed 20 .…”
Section: Resultsmentioning
confidence: 99%
“…WMA reporting has been variable among studies with incidence ranging from 14% to 26% among patients with COVID-19 who underwent ECHO, 50,62 and has shown to correlate with biochemical injury of the myocardium. 63,64 WMA was more frequently observed in the mid and apical segments followed by basal segments. 63,64 EKG changes are common, but do not always exist in patients with WMAs.…”
Section: Wall Motion Abnormality (Wma)mentioning
confidence: 90%
“…63,64 WMA was more frequently observed in the mid and apical segments followed by basal segments. 63,64 EKG changes are common, but do not always exist in patients with WMAs. The most common EKG change was T wave inversion.…”
Section: Wall Motion Abnormality (Wma)mentioning
confidence: 90%
See 1 more Smart Citation